2006
DOI: 10.1186/1475-2875-5-54
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of drug-resistance mutations in Plasmodium falciparum and Plasmodium vivax in southern Ethiopia

Abstract: BackgroundIn Ethiopia, malaria is caused by both Plasmodium falciparum and Plasmodium vivax. Drug resistance of P. falciparum to sulfadoxine-pyrimethamine (SP) and chloroquine (CQ) is frequent and intense in some areas.MethodsIn 100 patients with uncomplicated malaria from Dilla, southern Ethiopia, P. falciparum dhfr and dhps mutations as well as P. vivax dhfr polymorphisms associated with resistance to SP and P. falciparum pfcrt and pfmdr1 mutations conferring CQ resistance were assessed.ResultsP. falciparum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 22 publications
1
28
3
Order By: Relevance
“…The finding of this study does not support a previous study conducted in Ethiopia that reported a 100% frequency of the pfcrt T76 mutation, and an 81% frequency of the mutation pfmdr1 Y86 in P. falciparum [ 41 ] . However, the current finding is in line with studies conducted in two East African countries [ 27 , 42 ], where the frequency of the pfcrt -76 resistance alleles were repopulated with the sensitive ones after many years of CQ withdrawal.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The finding of this study does not support a previous study conducted in Ethiopia that reported a 100% frequency of the pfcrt T76 mutation, and an 81% frequency of the mutation pfmdr1 Y86 in P. falciparum [ 41 ] . However, the current finding is in line with studies conducted in two East African countries [ 27 , 42 ], where the frequency of the pfcrt -76 resistance alleles were repopulated with the sensitive ones after many years of CQ withdrawal.…”
Section: Discussioncontrasting
confidence: 99%
“…Concerning pfmdr1 , while wild-type pfmdr1 is thought to transport and accumulate CQ in the parasites’ food vacuole, mutations N86Y, S1034C, N1042D, and D1246Y interfere with transportation of the anti-malarial drugs, leading to reduced CQ-sensitivity [ 14 ]. The percentage of wild-type alleles at codon 86 of pfmdr1 was 85.1% (166/195), which is higher than 81% present in Schunk in 2006 and 84.5% in Eshetu in 2010 [ 41 , 52 ]. It should be clear that the study by Schunk in 2006 was conducted 7 years before the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, spread of insecticide-resistant vectors [19,20] and drug-resistant malaria parasites [21,22] may result in disease outbreaks. Therefore, control of larvae, which has so far been given little attention, should be reintroduced and implemented together with the existing strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Vivax malaria is an acute and painful disease that, unlike falciparum malaria, may relapse owing to a unique characteristic of the life cycles of P. vivax and P. ovale: the generation of dormant hypnozoites in the liver (Sattabongkot et al, 2004). Treatment for malaria includes sulfadoxinepyrimethamine, chloroquine, pyrimethamine and mefloquine, but drug resistance to these drugs is a growing concern and new drugs are urgently needed (Maguire et al, 2006;Schunk et al, 2006). To address this need, the Structural Genomics of Pathogenic Protozoans consortium (SGPP; http://www.sgpp.org) sought to determine protein structures from major tropical eukaryotic pathogens, including Plasmodium.…”
Section: Introductionmentioning
confidence: 99%